2016
DOI: 10.1210/en.2016-1242
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Reproductive and Developmental Health Outcomes Following Prenatal Exposure to a Hydraulic Fracturing Chemical Mixture in Female C57Bl/6 Mice

Abstract: Unconventional oil and gas operations using hydraulic fracturing can contaminate surface and groundwater with endocrine-disrupting chemicals. We have previously shown that 23 of 24 commonly used hydraulic fracturing chemicals can activate or inhibit the estrogen, androgen, glucocorticoid, progesterone, and/or thyroid receptors in a human endometrial cancer cell reporter gene assay and that mixtures can behave synergistically, additively, or antagonistically on these receptors. In the current study, pregnant fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 106 publications
0
26
0
Order By: Relevance
“…Concentrations tested were dependent on toxicity tested performed prior to bioassays to prevent potential erroneous interpretation of receptor antagonism due to toxicity; all concentrations tested exhibited no toxicity in MTT assay. Results for WV samples published previously; Kassotis et al, 2016, Endocrine disrupting activities of surface water associated with a West Virginia oil and gas industry wastewater disposal well; Science of the Total Environment. …”
Section: Figmentioning
confidence: 99%
See 2 more Smart Citations
“…Concentrations tested were dependent on toxicity tested performed prior to bioassays to prevent potential erroneous interpretation of receptor antagonism due to toxicity; all concentrations tested exhibited no toxicity in MTT assay. Results for WV samples published previously; Kassotis et al, 2016, Endocrine disrupting activities of surface water associated with a West Virginia oil and gas industry wastewater disposal well; Science of the Total Environment. …”
Section: Figmentioning
confidence: 99%
“…>1000 different chemicals are used for hydraulic fracturing across the US (Waxman et al, 2011; Environmental Protection Agency (EPA), 2015), many of which have been demonstrated to act as endocrine disrupting chemicals (EDCs) both in vitro and in vivo (Kassotis et al, 2014; Webb et al, 2014; Bolden et al, 2015; Kassotis et al, 2016a; Kassotis et al, 2015; He et al, 2017a; He et al, 2017b; Blewett et al, 2017a). EDCs are exogenous chemicals or mixtures of chemicals that can interfere with any aspect of hormone action (Zoeller et al, 2012; The Endocrine Disruption Exchange (TEDX), 2017; Diamanti-Kandarakis et al, 2009) and may disrupt development and contribute to disease in both humans and animals, particularly during critical windows of development (Vandenberg et al, 2012; Welshons et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the CPP was intended to address climate change by reducing greenhouse gas emissions, it would have also further affected ancillary air pollutants, including those linked to diabetes risk. Similarly, intriguing evidence now suggests that chemicals used in oil and gas extraction (e.g., hydraulic fracturing or “fracking”) function as EDCs with effects that include metabolic disruptions [61, 62]. Furthermore, these processes increase leaching of diabetogenic arsenic into groundwater [63].…”
Section: Challenges In Environmental Policy Influencing Diabetes Riskmentioning
confidence: 99%
“…Reproductive effects were seen in pups at all exposures levels. Male pups showed signs of hormonal disruption including lower sperm counts, increased testis weight, and increased blood testosterone levels, 31 while females showed reduced levels of prolactin, follicle-stimulating hormone, and luteinizing hormone 32 …”
Section: Tracking Contamination In the Environmentmentioning
confidence: 99%